2003
DOI: 10.1152/japplphysiol.00792.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vasoconstrictor response to whole body skin cooling is altered by time of day

Abstract: To test for a diurnal difference in the vasoconstrictor control of the cutaneous circulation, we performed whole body skin cooling (water-perfused suits) at 0600 (AM) and 1600 (PM). After whole body skin temperature (T(sk)) was controlled at 35 degrees C for 10 min, it was progressively lowered to 32 degrees C over 18-20 min. Skin blood flow (SkBF) was monitored by laser-Doppler flowmetry at three control sites and at a site that had been pretreated with bretylium by iontophoresis to block noradrenergic vasoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…While it is unknown whether time of day influences vasodilator responses to local skin heating, it has been shown that both reflex vasoconstriction and vasodilatation are modified by time of day (0500 h vs. 1500 h) (Aoki et al, 2001;Aoki et al, 2003). Consequently, the potential exists that differences between the present findings and those of Ciplak et al and Frantz et al may be related to diurnal variations.…”
Section: Experimental Considerationscontrasting
confidence: 48%
“…While it is unknown whether time of day influences vasodilator responses to local skin heating, it has been shown that both reflex vasoconstriction and vasodilatation are modified by time of day (0500 h vs. 1500 h) (Aoki et al, 2001;Aoki et al, 2003). Consequently, the potential exists that differences between the present findings and those of Ciplak et al and Frantz et al may be related to diurnal variations.…”
Section: Experimental Considerationscontrasting
confidence: 48%
“…In women, skin vascular reactivity depends on the phase of the menstrual cycle: progesteron resets the treshold for active cutaneous vasodilation (Charkoudian & Johnson, 2000). Furthermore, SkBF and the cutaneous microvascular reactivity are subject to diurnal rhytms (Aoki et al, 2003). Another modulator that resets the threshold for active cutaneous vasodilation is physical exercise (Johnson, 1996;Rowell, 1993) that is covered in more detail elsewhere in the chapter.…”
Section: Neural Control Mechanismsmentioning
confidence: 99%
“…For each site, cutaneous vascular conductance (CVC) was expressed as a percentage of CVC max (%CVC max ). This method of normalization was followed to reduce the effects of site-to-site differences in the absolute values of CVC and to refer values to the common characteristic of maximal vasodilation (Taylor et al 1984), thereby optimizing the ability to make day-to-day and site-tosite comparisons of responses (Aoki et al 1997a(Aoki et al , 2003.…”
Section: Passive Heat Stress After Sleep Deprivationmentioning
confidence: 99%